2016
DOI: 10.1007/s11357-016-9939-5
|View full text |Cite|
|
Sign up to set email alerts
|

Age at menarche and age at natural menopause in East Asian women: a genome-wide association study

Abstract: Age at menarche (AM) and age at natural menopause (ANM) are complex traits with a high heritability. Abnormal timing of menarche or menopause is associated with a reduced span of fertility and risk for several age-related diseases including breast, endometrial and ovarian cancer, cardiovascular disease, and osteoporosis. To identify novel genetic loci for AM or ANM in East Asian women and to replicate previously identified loci primarily in women of European ancestry by genome-wide association studies (GWASs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 53 publications
2
46
4
Order By: Relevance
“…A report from the Nurses’ Health Study (NHS) and NHS II found that age at natural menopause was associated with an increased risk of endometrioid tumors (RR=1.13, 95% CI: 1.04–1.22), but not serous invasive or mucinous tumors 29 . Studies conducted among populations with different distributions of age at menarche 99,111,118 and age at menopause 119 indicate differences in the genetic heritability of these factors across ancestral groups 120-122 . Regardless, the available evidence suggests that any magnitude of effect is likely small.…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…A report from the Nurses’ Health Study (NHS) and NHS II found that age at natural menopause was associated with an increased risk of endometrioid tumors (RR=1.13, 95% CI: 1.04–1.22), but not serous invasive or mucinous tumors 29 . Studies conducted among populations with different distributions of age at menarche 99,111,118 and age at menopause 119 indicate differences in the genetic heritability of these factors across ancestral groups 120-122 . Regardless, the available evidence suggests that any magnitude of effect is likely small.…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…Figure B,C show the overview of the MR study. We searched for AAM GWAS performed in Chinese population and found four articles . One of them was excluded because of incomplete data .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a total of 25 SNPs were selected as instrumental variables in MR analyses for the Chinese population. We extracted the estimation of their associations with AAM from the published articles (Table ) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations